Differential protein expression in seminal plasma from fertile and infertile males - Angela P Cadavid J; Angela Alvarez; Udo R Markert; Walter Cardona Maya (Journal of Human Reproductive Sciences, 2014)
Aim: The aim of this study was to analyze human seminal plasma proteins in association with male fertility status using the proteomic mass spectrometry technology Surface-Enhanced Laser Desorption Ionization Time-of-Flight (SELDI-TOF-MS). Materials and Methods: Semen analysis was performed using conventional methods. Protein profiles of the seminal plasma were obtained by SELDI-TOF mass spectrometry over a strong anion exchanger, ProteinChip® Q10 array. Results and Conclusion: We found statistically significant differences in motility and sperm count between fertile and infertile men. In addition, we observed ten seminal proteins that are significantly up-regulated in the infertile group. In conclusion, comparison of seminal plasma proteome in fertile and infertile men provides new aspects in the physiology of male fertility and might help in identifying novel markers of male infertility.